On a continued fraction of order twelve - Kahtan, Abdulrawf A. A.; Sathish, Kumar C.; Sharath, G.; Vasuki, K. R. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We present some new relations between a continued fraction $U(q)$ of order twelve (which is established byM. S. M. Naika et al.) and $U(q^n)$ for $n = 7,9,11\;\text{and}\; 13$.